Strange bedfellows: HIV-related stigma among gay men in Australia - De Wit, J.; Murphy, Dean; Adam, P.; Donohoe, S. (2012)
© Springer Science+Business Media Dordrecht 2013. All rights are reserved. HIV-related stigma and discrimination among gay men has remained largely under-researched. Also, there generally is a lack of research that directly compares the HIV-related stigma experienced by people living with HIV and the stigma expressed by people not living with HIV. This chapter reports on an online community study in Australia, undertaken to investigate and compare HIV-related stigma as experienced by HIV-positive gay men and expressed by non-HIV-positive gay men. From 1 December 2009 to 31 January 2010, the HIV Stigma Barometer Survey recruited 1,258 HIV-positive (17.0 %), HIV-negative (72.6 %), and HIV status unknown (10.4 %) gay men. Participants answered a range of questions regarding stigma-related attributions of responsibility, social distancing, negative emotional reactions, and sexual exclusion. Findings show that HIV-positive men overall experienced low levels of stigma, including attributions of responsibility and social distancing. However, they experienced higher levels of negative emotional reactions and in particular experienced exclusion as sexual or romantic partners. HIV-related stigma expressed by non-HIV-positive men was highly comparable to the experiences of HIV-positive men. These findings provide evidence of HIV-related stigma and a serostatus divide in the gay community. Stigma seems located primarily in the domain of sex and relationships, and this possible sexual divide may reflect and drive the adoption of serostatus-based risk reduction strategies. An important contribution of this study is its comparison and cross-validation of reports of experienced as well as expressed stigma in gay men. This was enabled by a new stigma measure that was informed by a conceptual analysis of the stigma concept and draws on existing scales.